Factors affecting energy expenditure and the efficiency of fuel utilization : feeding and exercise models - Lambert, Estelle Victoria (MRC/UCT RU for Exercise and Sport Medicine, 2018)
The first aim of this dissertation was to monitor both rat and human responses to short-term perturbations in energy balance brought about through food energy restriction and refeeding, exercise training and the cessation of exercise training or surgical lipectomy. The second aim of this dissertation was to identify factors which might explain differences in food energy intake in weight-matched, weight-stable "large and small eaters". The final aim of this dissertation was to identify factors which might explain differences in resting energy expenditure in a large sample of weight-stable men and women, including exercising and non-exercising persons, and including persons who may be regarded as "restrained eaters".